HUBUNGAN ANTARA MOTIVASI DAN STRES KERJA TERHADAP KINERJA AUDITOR : PERAN REKAN KERJA SEBAGAI VARIABEL MODERATING (STUDI PADA KANTOR AKUNTAN PUBLIK DI KOTA BATAM, PADANG, PEKANBARU) - Claudya Shelviana Angelina; Ria Nelly Sari; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of work stress on motivation and performance auditors with co-workers as a moderating variable. Hopefully this research can assist auditors in order to improve for better performance in the future, The sample used in this study is the auditor of a public accounting firm in Batam, Pekanbaru and Padang.Data collected by distributing questionnaires to 65 auditors working in 22 PAOs, but only 53 questionnaires were returned, and the questionnaire that can be processed only 48 questionnaires. Data were analyzed using multiple regression (multiple regression) and moderate regression (Moderate Regression Analysis-MRA) and processed using SPSS version 17.0. The results showed that motivation and work stress has an influence on the auditors performance. However, motivation and stress are moderated by co-workers do not affect performance.Keywords: motivation, job stress, co-workers and performance of auditors